Error Analysis on Students’ Writing in Using Simple Present Tense in Descriptive Text - Mukarromah, Maulidatul; Suryanto, Bradhiansyah Tri (Universitas Nurul Jadid, 2021)
The objectives of this study are to know the types of errors and the dominant error made by the students of the ten grade of SMA Istiqlal. The researcher used the descriptive qualitative method as the research methodology. The data was collected from the written test done by the researcher. Based on the analysis that has done by the researcher, the result of the study found that all of the students produce error by total error 92 errors which classified into omission 46 error (50%),Â 5 error in addition (5,43%),Â 33 errors in miss-formation (35,86%) and 8 error in miss-ordering (8,69%). Thus, the dominant error was happened in the omission error by total error 46 errors (50%). The source of the error that made by the students are from interlingal and intra-lingual. However most of the errors are from the inralingual source which total 84 errors and 8 errors from inter-lingual.